2019
DOI: 10.1039/c8sc04986f
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow-temperature photochemical synthesis of atomically dispersed Pt catalysts for the hydrogen evolution reaction

Abstract: Atomically dispersed Pt is prepared by photochemical synthesis at a record-low temperature of −60 °C, which exhibits ultrahigh catalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 44 publications
1
66
0
2
Order By: Relevance
“…The enhanced performance of Pt SACs compared to bulk Pt results from the charge transfer from Pt to adjacent C/N atoms, as reflected in the higher oxidation state of Pt in XANES and the Bader charge analysis, which leads to the change of unoccupied d orbitals of single Pt atoms, favoring the HER process . Interestingly, HER free energy diagrams of PtN x sites reveal that the binding strength of H* is weakened with an increase in H coverage of the Pt atom surface . Thus, simultaneously binding two or more H atoms on a single Pt atom to catalyze the HER process follows the Tafel mechanism.…”
Section: Atomically Dispersed Single Metal Site Electrocatalysis For mentioning
confidence: 99%
See 1 more Smart Citation
“…The enhanced performance of Pt SACs compared to bulk Pt results from the charge transfer from Pt to adjacent C/N atoms, as reflected in the higher oxidation state of Pt in XANES and the Bader charge analysis, which leads to the change of unoccupied d orbitals of single Pt atoms, favoring the HER process . Interestingly, HER free energy diagrams of PtN x sites reveal that the binding strength of H* is weakened with an increase in H coverage of the Pt atom surface . Thus, simultaneously binding two or more H atoms on a single Pt atom to catalyze the HER process follows the Tafel mechanism.…”
Section: Atomically Dispersed Single Metal Site Electrocatalysis For mentioning
confidence: 99%
“…Since Pt is highly stable in both acids and bases, it is difficult to isolate single Pt atoms by removing Pt clusters and nanoparticles through traditional acid‐leaching methods. Thus, several vacancy trapping methods have been developed to prepare atomically dispersed PtC x and PtN x sites, which exhibit lower overpotentials, a smaller Tafel slope, and offer considerably higher stability compared to that of the commercial Pt/C catalyst. The enhanced performance of Pt SACs compared to bulk Pt results from the charge transfer from Pt to adjacent C/N atoms, as reflected in the higher oxidation state of Pt in XANES and the Bader charge analysis, which leads to the change of unoccupied d orbitals of single Pt atoms, favoring the HER process .…”
Section: Atomically Dispersed Single Metal Site Electrocatalysis For mentioning
confidence: 99%
“…[90,91] According to previous literatures, many synthetic techniques have been documented for downscaling metal NPs on the support, such as thermal decomposition and iced-photochemical reduction methods. [92][93][94] Through thermal decomposition, Corma and coworkers successfully realized the transformation from Pt NPs to single Pt atoms by O 2 activation ( Figure 1). [93] It has been demonstrated that the resultant single-atom Pt can obviously enhance the reaction kinetics due to the high dispersion of isolated Pt atoms on high-silica chabazite.…”
Section: Transforming Nps and Clusters To Single Atomsmentioning
confidence: 99%
“…Wu et al also found that the iced-photochemical technique exhibited great potential in downsizing metal NPs. [94] As compared with the conventional photochemical method, this novel synthesis technique can well fragment metal NPs into smaller NPs and even atomically dispersed metals, which would occupy a vitally important status in the fabrication of efficient and durable SACs.…”
Section: Transforming Nps and Clusters To Single Atomsmentioning
confidence: 99%
“…The agglomeration of metal single atom can be avoided from the perspective of kinetics and thermodynamics by this method, which supplements the traditional nucleation theory and provides a new idea for the synthesis of various metal single atoms. Subsequently, combining this method with photoreduction, atomic‐level dispersed Pt catalyst can be prepared in ethanol solution for efficient hydrogen evolution reaction . The effects of temperature on the nuclear barrier of Pt single atom are analyzed by first‐principles molecular dynamics method combined with constrained minimization simulation technology.…”
Section: Controllable Synthesis Of Nonprecious Metal Sa‐npc Catalystsmentioning
confidence: 99%